2021
DOI: 10.1155/2021/8891643
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Arsenic Removal from Aqueous Solution by Fe/Mn-C Layered Double Hydroxide Composite

Abstract: A novel material named Fe/Mn-C layered double hydroxide composite (Fe/Mn-C-LDH) was synthesized to remove arsenic from an aqueous solution. The removal performance of the composite toward arsenic ions was studied through the batch experiments. The experiment results showed that Fe/Mn-C-LDH exhibited a high adsorption capacity of 46.47 mg/g for As(III) and 37.84 mg/g for As(V) at 318 K, respectively. In addition, the investigation of the release of Fe3+ and Mn2+ in the process of arsenic adsorption revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Table S6 presents the results of calculations made about the thermodynamic characteristics of the adsorption of ACT onto HPN-2. The negative Δ G values at all temperatures showed the spontaneity of the ACT adsorption process onto HPN-2 . The Δ H > 0 of the ACT adsorption process demonstrated that the adsorption onto HPN-2 was an endothermic process .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Table S6 presents the results of calculations made about the thermodynamic characteristics of the adsorption of ACT onto HPN-2. The negative Δ G values at all temperatures showed the spontaneity of the ACT adsorption process onto HPN-2 . The Δ H > 0 of the ACT adsorption process demonstrated that the adsorption onto HPN-2 was an endothermic process .…”
Section: Resultsmentioning
confidence: 92%
“…The negative ΔG values at all temperatures showed the spontaneity of the ACT adsorption process onto HPN-2. 47 The ΔH > 0 of the ACT adsorption process demonstrated that the adsorption onto HPN-2 was an endothermic process. 48 Furthermore, the positive values of ΔS indicated the increasing randomness and the good binding affinity of HPN-2 for the adsorption of ACT.…”
Section: Adsorption Isotherm Of Act Onto Hpn-2mentioning
confidence: 98%
“…(S7)-(S10) mentioned in Table S4 (supplementary material). The negative estimation of G listed in Table 4 indicates the spontaneous adsorption of Cr(VI) onto the adsorbent and thermodynamic feasibility of the adsorption process [44]. A positive value of H indicates that the process is endothermic in nature.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe/Mn-C-LDH was more stable than the Fe/Mn-layer twofold hydroxide (Fe/Mn-LDH), with less Mn 2+ and Fe 3+ being released under the same conditions. According to the BET data, the adsorption of arsenic(III) and arsenic(V) onto Fe-Mn-C-LDH reduced its specific surface area [108]. Among both composites, HNTs/C/Fe 3 O 4 showed the best performance because of their unique heterojunction.…”
Section: Carbon-based Nanocomposites For Removing Industrial Pollutantsmentioning
confidence: 99%